Influence of HLA-DQ Matching on Allograft Outcomes in Deceased Donor Kidney Transplantation - N. Khongjaroensakun (2019)
© 2018 Elsevier Inc. Background and Objectives: HLA matching at the A, B, and DR loci influences the graft survival rate of deceased donor kidney transplants. The effect of HLA-DQB1 matching on transplant outcomes is still controversial. The aim of this study was to investigate the association of HLA-DQB1 matching with allograft outcomes in deceased donor kidney transplant recipients. Methods: A retrospective analysis of deceased donor kidney transplant recipients between 2008 and 2014 at the Faculty of Medicine Ramathibodi Hospital, Bangkok, Thailand, was performed. Donor-recipient HLA matching at DQB1 locus was analyzed. The association between HLA-DQB1 mismatches and transplant outcomes was investigated using adjusted Cox regression analysis. Results: A total of 383 deceased donor kidney transplants were performed during the study period, of which 297 with complete clinical and laboratory data were analyzed. The median follow-up time of all patients was 41 months (range, 16.4–65.6 months). Of the 297 recipients, 107 (36.03%) received 0 HLA-DQB1 mismatched kidneys and 190 (63.97%) received 1 or 2 HLA-DQB1 mismatched kidneys. Recipients who have received 1 or 2 HLA-DQB1 mismatched kidneys had a higher risk of acute rejection, with the adjusted hazard ratio of 4.35 (95% CI, 1.41–13.42; P =.01). However, HLA-DQB1 mismatching was not associated with chronic rejection and graft survival. Conclusion: Donor-recipient HLA-DQB1 mismatching is associated with acute rejection in deceased donor kidney transplants. However HLA-DQB1 mismatching does not have a negative impact on chronic rejection or graft survival.